Influences of Hillslope Biogeochemistry on Anaerobic Soil Organic Matter Decomposition in a Tundra Watershed. Issue 7 (10th July 2020) - Philben, Michael; Taş, Neslihan; Chen, Hongmei; Wullschleger, Stan D.; Kholodov, Alexander; Graham, David E.; Gu, Baohua
Abstract: We investigated rates and controls on greenhouse gas (CO2 and CH4 ) production in two contrasting water‐saturated tundra soils within a permafrost‐affected watershed near Nome, Alaska, United States. Three years of field sample analysis have shown that soil from a fen‐like area in the toeslope of the watershed had higher pH and higher porewater ion concentrations than soil collected from a bog‐like peat plateau at the top of the hillslope. The influence of these contrasting geochemical and topographic environments on CO2 and CH4 production was tested in soil microcosms by incubating both the organic‐ and mineral‐layer soils anaerobically for 55 days. Nitrogen (as NH4 Cl) was added to half of the microcosms to test potential effects of N limitation on microbial greenhouse gas production. We found that the organic toeslope soils produced more CO2 and CH4, fueled by higher pH and higher concentrations of water‐extractable organic C (WEOC). Our results also indicate N limitation on CO2 production in the peat plateau soils but not the toeslope soils. Together these results suggest that the weathering and leaching of ions and nutrients from tundra hillslopes can increase the rate of anaerobic soil organic matter decomposition in downslope soils by (1) increasing the pH of soil porewater; (2) providing bioavailable WEOC and fermentation products such as acetate; and (3) relieving microbial N limitation through nutrient runoff. We conclude that the soil geochemistry as mediated by landscape position is an important factor influencing the rate and magnitude of greenhouse gas production in tundra soils. Key Points: We compared CO2 and CH4 production in soils from two wetland areas along a tundra hillslope gradient (toeslope and peat plateau) Production of both gasses was higher in the organic toeslope soils, while microbial N limitation was higher in peat plateau soils Downslope transport of N, DOM, and alkalinity increases greenhouse gas production in the organic toeslope soils